EP609 The prognostic role of LRIG proteins in endometrial cancer. (1st November 2019) - Razumova, Z; Oda, H; Govorov, I; Lundin, E; Östensson, E; Lindquist, D; Mints, M
Abstract : Introduction/Background: Endometrial cancer (EC) is the most common gynaecological malignancy in Sweden. The disease has several prognostic factors. Still, the high amount of EC develops into more aggressive forms of cancer, even though being first considered to be non-aggressive. The LRIG proteins are a family of three integral surface proteins that have a similar domain organisation. The current study evaluated the role of LRIG proteins as prognostic biomarkers in EC. Methodology: The cohort included 75 women who underwent a hysterectomy and bilateral salpingo-oophorectomydue to EC at the Department of Women's and Children's Health, Karolinska University Hospital Solna between 2007 and 2012. The expression of LRIG1, LRIG2, and LRIG3 in paraffin biopsies was analysed by immunohistochemistry (IHC) with applying specific polyclonal antibodies. Evaluation of immunostainings was performed by two senior pathologists without knowledge of the disease outcome.The percentage of positive cells was divided in two groups with median percentage as cut off to have two groups of equal size included in the statistical analysis. Then the groups were assessedin connection with different tumour characteristics and clinical outcomes of EC. Results: The majority of women in the cohort had >50% LRIG1-, LRIG2-, and LRIG3-positive cells. Among 6047 person-months of follow-up a total, of 14 incident cases of relapsed EC were identified. A statistically significant association between high LRIG3 expression and superior overall survival was observed in the cohort (IRR=2.559, 95 CI=1.054–6.210, p=0.038). LRIG1 and LRIG2 expression did not significantly correlate with survival. Conclusion: Our results support the hypothesis that LRIG3 expression may have a prognostic role in women with EC. The significance of LRIG1 and LRIG2 expression remains to be clarified. Disclosure: Nothing to disclose.